Odpowiedzi

2010-01-26T17:57:42+01:00
A) -2a+b-a-2b+3a = -2a-a+3a+b-2b = -b
b) -ab+b²+3ab-2ab = -ab+3ab-2ab+b² = b²
c) 2/3x+1/3y+2 i 1/3x-1/3y = 2/3x+2⅓x+1/3y-1/3y = 3x
d) 15xy-4x+8y-6xy+5x-xy = 15xy-6xy-xy-4x+5x+8y = 8xy+x+8y
e) 0,2x²-2y+1,8x²+4,3y-x = 0,2x²+1,8x²-x-2y+4,3y = 2x²-x+2,3y
f) -1/4m+1/8n-1/8m+0,375m = -1/4m-1,8m+0,375m+1/8n = -1,675m+1/8n
2010-01-26T18:53:45+01:00
-2a+b-a-2b+3a = -2a-a+3a+b-2b = -b

-ab+b²+3ab-2ab = -ab+3ab-2ab+b² = b²

2/3x+1/3y+2 i 1/3x-1/3y = 2/3x+2⅓x+1/3y-1/3y = 3x

15xy-4x+8y-6xy+5x-xy = 15xy-6xy-xy-4x+5x+8y = 8xy+x+8y

0,2x²-2y+1,8x²+4,3y-x = 0,2x²+1,8x²-x-2y+4,3y = 2x²-x+2,3y